PO meds oral & EEN medication administration - Indiana University. School of Nursing (Indiana : University of Indiana, 1999)
Developed to teach health professionals how to administer oral and EEN medications.
Developed by Indiana University School of Nursing.
System requirements: IBM-compatible 486 DX2-66 or higher processor; 8 MB RAM (16 MB recommended); Windows 95, 98, or NT; 256 col. video card (higher col. resolution recommended); sd. card; CD-ROM (at least 4x).
Keywords: Administration, Topical; Administration, Oral